Knowledge Description on The Use of Energy Drinks in The Students of Medical Faculty of YARSI University and Its Review According to Islamic View - Muhammad Hafids Shulthon; Dharma Permana (Junior Medical Journal, 2022)
Background: Energy drinks contain caffeine and energy source from sucrose (sugar) or maltodextrin. Energy drinks also contain vitamins that are involved in body's metabolism to produce energy. Several studies have shown that consumption of energy drinks has a negative impact on health if consumed continuously. Consumption of energy drinks is one of the risk factors for chronic kidney failure. This research was conducted to find out the overview of knowledge regarding the consumption of energy drinks in the Faculty of Medicine students at YARSI University.Method: This type of research uses analytic survey method with cross sectional research design which is intended to know the description of students' knowledge by using questionnaires taken directly through students who have inclusion criteria namely have consumed energy drinks more than two months before the study was conducted and were willing to be respondents. The sample size was determined by using the Slovin formula and the sample was determined by using non-random purposive sampling technique.Results: Based on the results of the study, the number of respondents was 89 students. From the data collected there were 40 students (44.9%) with sufficient knowledge category, with 27 people (30.3%) good knowledge category and 22 people (24.7%) in the lack category. 49 people (55.1%) feel fresher, 18 people (20.2%) do not feel any effect, 8 people (9%) feel focused, 8 people (9%) feel insomnia and 6 people feel headaches (6.7%). P value of 0.86 and chi-square value of 11.067. Because the significance value is 0.86 ( 0.05), there is no significant relationship between the Force and Knowledge Level.               Conclusion: The respondents' level of knowledge and consumption of energy drinks is quite good. In Islam, the consumption of energy drinks is permissible as long as it does not contain alcohol and substances that are harmful to the body.